THE EFFICACY OF MOTORCYCLE TRAINING TO REDUCE SELF-REPORTED NEGATIVE BEHAVIOUR AND ATTITUDE (CASE STUDY IN UK AND INDONESIA) - Winna Justiana Sirait; Sigit Priyanto; Samantha Jamson (Journal of the Civil Engineering Forum, 2014)
Motorcyclists are vulnerable road users because of their particular combination of physical vulnerability. Motorcyclists’ training and licensing system have already implemented in so many countries in the world particularly developed countries. In the other hand, there are countries, particularly developing countries, where motorcyclists are less regulated in term of licensing, enforcement, and insurance. Therefore the objective of this research are to analyses the behavior and attitude of motorcyclists in Yorkshire and Humber Region (UK) and Jakarta (Indonesia), and to analyses the efficacy of motorcycle training in UK to influence the self-reported negative behavior and attitude of motorcyclists.Motorcycle Rider Behavior Questionnaire (MRBQ) and Motorcyclists Attitude Questionnaire (MAQ) are used to conduct this study. The Mann Whitney test is used to evaluate the significance different of the mean score, which obtained from the survey in each country (UK and Indonesia).Mean score computation showed that Yorkshire and Humber Region’s respondents have better mean score than Jakarta’s respondents. However Mann Whitney test showed that the mean score different is not significant for speed violation factor in MRBQ and drink driving and speeding factor in MAQ.Keywords: motorcyclist, motorcycle training, Motorcycle Rider Behavior Questionnaire (MRBQ), Motorcyclist Attitude Questionnaire (MAQ).